The NCBI BioCollections Database. (23rd February 2018) - Sharma, Shobha; Ciufo, Stacy; Starchenko, Elena; Darji, Dakshesh; Chlumsky, Larry; Karsch-Mizrachi, Ilene; Schoch, Conrad L
Abstract: The rapidly growing set of GenBank submissions includes sequences that are derived from vouchered specimens. These are associated with culture collections, museums, herbaria and other natural history collections, both living and preserved. Correct identification of the specimens studied, along with a method to associate the sample with its institution, is critical to the outcome of related studies and analyses. The National Center for Biotechnology Information BioCollections Database was established to allow the association of specimen vouchers and related sequence records to their home institutions. This process also allows cross-linking from the home institution for quick identification of all records originating from each collection. Database URL : https://www.ncbi.nlm.nih.gov/biocollections